Integrated multi-omics identify key signalling pathways for notochord lumenogenesis in ascidian Ciona savignyi - Jin Zhang; Zicheng Tan; Qishu Qin; Hongzhe Peng; Wenjie Shi; Haiyan Yu; Bo Dong (Open Biology)
Lumen formation and inflation are crucial for tubular organ morphogenesis and function. However, the key signalling pathways for lumenogenesis regulation were not well identified. Here, we performed tissue-specific transcriptomic sequencing for the isolated Ciona notochord tissue, in which 10 551 genes in total were identified. To investigate crucial signalling pathways in regulating lumenogenesis, KEGG was performed and the results showed that the Rap1 signalling pathway, vascular endothelial growth factor signalling pathway, mitogen activated protein kinase (MAPK) signalling pathway (plant) and Ras signalling pathway might play important roles in lumenogenesis. Moreover, correlation analysis with proteomic data and comparison analysis of single-cell transcriptomic data were further utilized to identify the potential critical roles of the Rap1 signalling pathway and Ras signalling pathway in lumenogenesis. To verify their functions in lumenogenesis, the Ras/calcium-Rap1-MAPK signalling axis was blocked, and the results showed that the notochord lumenogenesis failed. Meanwhile, we identified that CDC42 was a potential downstream target factor of the Ras-Rap1-MAPK signalling axis, playing crucial functions in notochord lumenogenesis. Overall, we systematically revealed the key regulatory signalling pathways for notochord lumen formation and verified a lumenogenesis-related signalling axis, providing a foundational data resource for exploring the mechanisms of lumenogenesis.